Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/bju.15667
|View full text |Cite
|
Sign up to set email alerts
|

Online urological educational material for medical students: can search engines be trusted?

Abstract: Objectives To determine the credibility of online urological information that medical students are likely to encounter, determine possible discrepancies between the credibility of information pertaining to different areas within urology (especially those less relevant to patients), and assess trends in the sponsorship of online urological educational material. Materials and Methods Health on the Net (HON) principles were used as a validated benchmark to assess the reliability of websites that appeared in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our study focused exclusively on video‐sharing platforms as a source of information for patients; however, YT and TK exist within the wider context of the internet. In a recent study, Gunasegaram et al reviewed 5400 webpages to evaluate the quality of online urology information 37 . They found that online information frequently lacks validation and is of indeterminate credibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study focused exclusively on video‐sharing platforms as a source of information for patients; however, YT and TK exist within the wider context of the internet. In a recent study, Gunasegaram et al reviewed 5400 webpages to evaluate the quality of online urology information 37 . They found that online information frequently lacks validation and is of indeterminate credibility.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Gunasegaram et al reviewed 5400 webpages to evaluate the quality of online urology information. 37 They found that online information frequently lacks validation and is of indeterminate credibility. Similarly, Loeb et al compared the quality of prostate cancer information on 150 YT videos with that on 150 websites and found that most content did not meet quality criteria for health information.…”
Section: Discussionmentioning
confidence: 99%